Influence of culturing conditions for optimum antimicrobial metabolite production by Streptomyces fulvoviridis (Chittagong University Journal of Biological Sciences, 2013)
Chili field antagonistic actinomycetes Streptomyces fulvoviridis was isolated and tested for optimum antimicrobial metabolite production. Maximum antimicrobial metabolite production was found at temperature 35°C and pH 8.0 and on 4th day of incubation in shaking condition. The medium consisting of beef extract - 0.75%, peptone - 0.25%, NaCl - 1.5%, KCl - 1.0%, MgCl2 - 1.0%, FeSO4 - 1.0% was screened out as suitable medium for maximum antimicrobial production supplemented individually with four carbon sources of which sucrose was found as the best carbon source. The antimicrobial metabolite was found to be stable at pH and temperature up to 11.0 and 100ºC, respectively. The active agent was best extracted with chloroform. The antimicrobial spectrum of the metabolite was wide and shows activity against - Shigella dysenteriae (AE 14612), Shigella sonnei (CRL, ICDDR, B), Salmonella typhi (AE14296), Vibrio cholerae (AE14748), Pseudomonas aeruginosa (CRL, ICDDR, B), Bacillus cereus (BTCC19), Staphylococcus aureus (ATCC6538), Bacillus subtilis (BTTC17) and Bacillus megaterium (BTTC18). DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13371 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):63-75, 2010